2021
DOI: 10.1002/jez.2474
|View full text |Cite
|
Sign up to set email alerts
|

LPS‐induced immunomodulation and hormonal variation over time in toads

Abstract: The inflammatory response is a complex process that relies on interactions among multiple endocrine and immune modulators. Studies incorporating time-related and integrative endocrine and immune responses to an immune challenge might shed light on the characterization of the phases of the inflammatory response in anurans. The present study investigated time-related changes (1, 3, 6, and 18 h post-challenge) in plasma corticosterone (CORT), melatonin (MEL) and testosterone (T) levels, phagocytosis percentage (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 74 publications
(110 reference statements)
0
3
0
1
Order By: Relevance
“…Moreover, Titon Junior et al . [64] demonstrated that body index was positively associated with BKA and percentage phagocytosis after lipopolysaccharide injection in R. diptycha . Herein, potential interactions between body condition and T-induced immunomodulation were not found in T-treated R. icterica toads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Titon Junior et al . [64] demonstrated that body index was positively associated with BKA and percentage phagocytosis after lipopolysaccharide injection in R. diptycha . Herein, potential interactions between body condition and T-induced immunomodulation were not found in T-treated R. icterica toads.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, individuals of R. icterica maintaining body index under long-term captivity also showed a positive association between T and percentage phagocytosis [43]. Moreover, Titon Junior et al [64] demonstrated that body index was positively associated with BKA and percentage phagocytosis after lipopolysaccharide injection in R. diptycha. Herein, potential interactions between body condition and T-induced immunomodulation were not found in T-treated R. icterica toads.…”
Section: (B) Testosterone Transdermal Applicationmentioning
confidence: 94%
“…Stress-driven immunomodulation has gained more attention in ectothermic vertebrates in the last decades [25,27,39,[56][57][58][59][60][61][62], with implications on the stress-induced protective and harmful effects on several immune functions. As observed in other vertebrates, the amphibian immune system is subjected to stressors and its endocrine mediators, including glucocorticoid-induced immunomodulation [27,28,31,32,63,64].…”
Section: Stress-related Immunomodulationmentioning
confidence: 99%
“…A ação específica do LPS no organismo de anuros é pouco esclarecida em detalhes na literatura, mas já foi observado que anuros injetados com LPS apresentam em seus níveis plasmáticos glicocorticóides e moléculas pró-inflamatórias como as citocinas (IL-1β, IL-6, TNF-α), que desencadeiam uma resposta inflamatória e levam as alterações comportamentais comentadas Junior et al, 2021;.…”
Section: Ação E Efeito Do Lps Após Simulação De Infecçãounclassified